Analysis of hysteresis properties in a polyurethane insulator applied to simulated structural models on the Sailham shake table - Erazo Hernández, Ramiro Humberto; Cando Erazo, Brian Oswaldo (SATHIRI, 2023)
The current investigative study aims to find the hysteresis properties of a material that allows to resemble the behavior of an insulator, it will be incorporated into three experimental models of different material and configuration. The acceleration responses were determined experimentally, by simulating on the Sailham shake table for four thrusting seismic events and four subduction events, each with two stages. To measure the acceleration responses, an accelerometer was placed on each lintel of the isolation floor. With the data obtained from the experimentation, the displacements and forces were determined through mathematical processes, in order to elaborate the hysteresis curve of the insulators of each experimental model. From the hysteresis curve, the properties of the polyurethane insulator were obtained, such as damping and effective stiffness, and with this, analyze the theory of seismic isolation.
Keywords: Hysteretic properties; isolator; hysteresis curve; polyurethane